2022
DOI: 10.3390/toxics10060316
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of Cu2+, Cd2+ and Pb2+ by Modified Wheat Straw Biochar from Aqueous Solution: Preparation, Characterization and Adsorption Mechanism

Abstract: As an eco-friendly and efficient adsorbent for removal of potential toxic metals from aqueous solution, biochar has received widespread attention. In the present study, wheat straw biochar (BC) and corresponding modified biochar (HNC) were used to remove Cu2+, Cd2+ and Pb2+ from an aqueous solution. The influence of the environment factors on metals adsorption and adsorption mechanism were discussed in detail. The results showed that the HNC had porous structures and owned ample functional groups (−OH, −COOH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…The analysis of the surface of biochar with particle sizes ranging from 2.00 to 2.38 mm revealed that it had a Brunauer-Emmett-Teller (BET) specific surface area (SSA) value of 2.83 m 2 /g and a total pore volume of 1.40 × 10 −3 cm 3 /g ( Table 1 ), which is comparable with some values obtained in previous studies. 48 , 49 The content of ashes in the resulting biochar may hinder pore development during carbonization, which could explain the low values reported by BET analysis. BCCPH has an average pore diameter of 1.98 nm, which is approximately twice the diameter of a hydrated Cd ion (0.852 nm) and around 10 times the diameter of a bare Cd ion (0.194 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the surface of biochar with particle sizes ranging from 2.00 to 2.38 mm revealed that it had a Brunauer-Emmett-Teller (BET) specific surface area (SSA) value of 2.83 m 2 /g and a total pore volume of 1.40 × 10 −3 cm 3 /g ( Table 1 ), which is comparable with some values obtained in previous studies. 48 , 49 The content of ashes in the resulting biochar may hinder pore development during carbonization, which could explain the low values reported by BET analysis. BCCPH has an average pore diameter of 1.98 nm, which is approximately twice the diameter of a hydrated Cd ion (0.852 nm) and around 10 times the diameter of a bare Cd ion (0.194 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The Langmuir model and Freundlich model were used to fit the isothermal adsorption data and are expressed by Formulas (3) and (4) [ 40 ]: where C e refers to the concentration of ReO 4 − at equilibrium (mg/L), Q max is the theoretical maximum adsorption capacity (mg/g), K L is the Langmuir constant (L/mg), and K F (mg/g (L/mg)1/n) and 1/n are Freundlich constants.…”
Section: Methodsmentioning
confidence: 99%
“…Além dos modos de produção vários tratamentos na biomassa pré e pós pirólise tem sido realizados com o intuito de melhorar sua capacidade de remediação de solos e águas. Os métodos mais comumente utilizados para modificar e aumentar a eficiência do biocarvão na remoção de poluentes do solo e da água são: tratamento ácido ou oxidação (remoção de matéria orgânica não pirolizada e das cinzas dos poros, aumento da área superficial e dos grupos funcionais carboxyl) e básico (remoção e matéria orgânica não pirolizada e das cinzas dos poros, aumento da área superficial e dos grupos funcionais hydroxyl), amination, ativação por vapor (remoção e matéria orgânica não pirolizada dos poros com aumento da área superficial e dos grupos funcionais hydroxyl), produção de biocarvão com cobertura de óxidos (aumento das cargas superficiais positivas), matéria carbonácea, argilas (aumento das capacidades de adsorção de oxyanions e cátions poliatômicos), compostos orgânicos (aumento da capacidade e da energia na adsorção de metais) e biofilmes de grafeno e nanotubos de carbono (aumento da área superficial e dos grupos funcionais contendo oxigênio) (Rajapaksha et al, 2016;Sizmur et al, 2017;Li et al, 2017;Huang et al, 2021, Hamid et al, 2022Wang et al, 2022;Yu et al, 2022).…”
Section: Introductionunclassified